2022
DOI: 10.1001/jamanetworkopen.2022.4514
|View full text |Cite
|
Sign up to set email alerts
|

Association of a Zero-Separation Neonatal Care Model With Stress in Mothers of Preterm Infants

Abstract: Key Points Question Is there an association between the neonatal care setting—a family integrated care (FICare) model in single family rooms with complete couplet-care for the mother-newborn dyad vs standard neonatal care in open bay units—and mental health and participation outcomes among mothers of preterm newborns? Findings In this cohort study of 296 mothers of preterm infants, mothers reported experiencing less stress and participated more when they an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 66 publications
3
16
0
2
Order By: Relevance
“…Our funding showed that maternal stress in both groups was reduced significantly, and the reduction percentage of FICare group was higher than that of the control group. Our results were consistent with those of previous studies (O'Brien et al, 2018; van Veenendaal et al, 2022). In the early life of pups, their growth and development were mostly restricted to the activities of their mothers (Bebbington & Groothuis, 2021).…”
Section: Discussionsupporting
confidence: 94%
“…Our funding showed that maternal stress in both groups was reduced significantly, and the reduction percentage of FICare group was higher than that of the control group. Our results were consistent with those of previous studies (O'Brien et al, 2018; van Veenendaal et al, 2022). In the early life of pups, their growth and development were mostly restricted to the activities of their mothers (Bebbington & Groothuis, 2021).…”
Section: Discussionsupporting
confidence: 94%
“…Future research should focus on the different (aspects of) care concepts, themes, and workplace cultures we encountered in our study, the fidelity of care models, and the potential pathways towards outcomes of parents and their infants with for instance network meta‐analyses 48 , 49 or mediation analyses. 14 , 50 As much data is arising on the benefits of parent participation in care and zero‐separation, 10 , 11 , 14 , 15 , 50 next studies should work with methods from an implementation science point of view to promote the systematic uptake of these clinical research findings into routine neonatal care. 51 Additionally, research should focus on an exact definition and measurement of “zero‐separation” in this context, as one can still feel emotionally connected without being physically present.…”
Section: Discussionmentioning
confidence: 99%
“…However, currently, there is no standardized practice model in the US which fully incorporates parents as members of the care team. Family Integrated Care (FICare) is a novel approach utilized in other countries that is based on PFCC principles but provides a practice framework to integrate parents as care team members [ 18 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies conducted in those countries, as well as in others with similar healthcare systems, reported numerous positive effects of FICare participation including increased infant weight gain and exclusive breastfeeding rates, reduced length of stay, improved parent confidence and increased involvement in newborn care, better parental-newborn bonding, as well as lower parental stress, lower anxiety and lower paternal depressive symptoms [ 20 , 22 26 ]. Similarly, follow-up studies showed improved behavioral skills and outcomes, improved neurodevelopmental outcomes, and lower maternal stress scores at 18 months post-conceptual age [ 27 30 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation